Coffee brands, class and culture in a Canadian city. (August 2013) - Bookman, Sonia
This article draws on a dynamic, cultural approach to class, as well as recent theoretical developments within the sociology of brands, to explore some of the ways that social class is being made and remade on the platforms of brands. It focuses on the three most prominent coffeehouse brands in Canada, and draws on substantial qualitative data from a study conducted in the city of Winnipeg. Examining the brands, it shows how they offer consumers distinctive, themed experiences such as 'cosmopolitan connoisseurship' that shape meanings and practices of coffee consumption. Using material from interviews with consumers and employees of the brands, it illustrates how consumers draw on the brands and the cultural frames they afford as a means to co-construct notions of class and perform distinction. This occurs in a complex brand–consumer dynamic in which class antagonisms are expressed and boundaries co-produced in the specific arena of coffee consumption.